2008
DOI: 10.1017/s0022215108003964
|View full text |Cite
|
Sign up to set email alerts
|

Impact of isotonic and hypertonic saline solutions on mucociliary activity in various nasal pathologies: clinical study

Abstract: Nasal irrigation with isotonic or hypertonic saline can improve mucociliary clearance time in various nasal pathologies. However, these solutions should be selectively prescribed rather than used based on anecdotal evidence. Further studies should be conducted to develop a protocol for standardised use of saline solution irrigation in various nasal pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 17 publications
1
79
0
15
Order By: Relevance
“…Unlike the abovementioned results, Ural et al (18) showed that nasal irrigation with isotonic saline improved the nasal MCC of allergic patients. However, Kim et al (36) studied the effects of irrigation with three different saline concentrations on cell morphology and mucin secretion in human nasal epithelial cell cultures and found that the group submitted to isotonic saline irrigation exhibited a normal epithelium covered in healthy cilia and preserved cellular integrity, thus favoring MCC.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Unlike the abovementioned results, Ural et al (18) showed that nasal irrigation with isotonic saline improved the nasal MCC of allergic patients. However, Kim et al (36) studied the effects of irrigation with three different saline concentrations on cell morphology and mucin secretion in human nasal epithelial cell cultures and found that the group submitted to isotonic saline irrigation exhibited a normal epithelium covered in healthy cilia and preserved cellular integrity, thus favoring MCC.…”
Section: Discussionmentioning
confidence: 86%
“…This result corroborates the concept proposed by Harvey et al (19), whereby large volumes of saline under positive pressure are needed for mechanical clearance to occur. According to the authors, liquid saline instillation under high pressure generates the shear force needed to alter gas-liquid interaction, which favors the removal of viscous mucus adhered to the walls of the airways, inflammatory cells, pollutants and bacteria (12,18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice of continuous infusion is supported by 1 retrospective study in children, as well as some case reports in adult patients. 8 Patients undergoing Magnesium sulfate dressing did not show much improvement after first dressing. 9 Bridie O Sullivan manage cellulitis by hydrofibre dressing which maintained the moist wound environment and promoted autolytic debridement.…”
Section: Discussionmentioning
confidence: 92%
“…В некоторых работах подчеркивается необходимость щадящего отношения к СО при туалете полости носа, в част ности следует избегать грубой работы отсосом. Хо рошо зарекомендовали себя и часто используются пациентами изотонические солевые растворы, ув лажняющие СО полости носа и разжижающие ско пившееся отделяемое [38]. Ряд авторов используют местно различные препараты, в частности антибак териальные мази [39].…”
unclassified